Penyelesaian Sengketa Pelaksanaan Perjanjian Lelang Sungai di Bidang Perikanan di Kecamatan Tanjung Lago Kabupaten Banyuasin - Indrajaya Indrajaya (Wajah Hukum, 2021)
In the Civil Code regulates agreement, one type of agreement is an auction, however the object of this auction agreement is not an object or animal, but a river. In areas that have natural resources in the form of rivers, these agreements are often carried out, in practice adapted to local local wisdom. The river auction tradition in Tanjung Lago District, Banyuasin Regency, South Sumatra Province has been going on for a long time and has become a tradition for the local population. However, in practice there are often defaults committed by the parties. The purpose of this study is to determine the settlement of disputes in case of default by the parties. The research method is to look at direct facts that happen in real terms but still by using legal materials in the form of existing regulations and other sources. From the research results it is known that if one of the parties (the village administration and the winner of the auction) defaults, a deliberation between both parties but if it cannot be resolved then legal action can be taken. Meanwhile, if there is a default between the auction winner and the fisherman, the settlement will only be in the form of a warning and loss of trust without any sanctions.